Using Analytical Hierarchy Process to Select the Best Power Generation Technology in Libya (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Selection of an appropriate power generation technology is a complex process. Because it is necessary to consider and take into account a wide range of parameters. The investment in the power generation field is too costly while resources are limited. This paper presents the determination of these parameters, which influence the selection of power generation technology in particular for developing countries. This paper answers the question of the best suitable technology for Libya because the investment in this field is so costly and making a wrong decision is not allowed, otherwise it will consume the big margin of the initial budget. Four main criteria are included, that is economic, environmental, technical and social. A sub-criteria are also included to support this decision. The performances of six technologies of a power generation are evaluated by Analytic Hierarchy Process (AHP) using expert choice software and the best technology is selected. The results showed that the solar photovoltaic power generation is the best technology. By means of the sensitivity analysis, it was found that the best alternative is not sensitive to a change in the weights estimated by the AHP.